ABOUT CONTACT PROBLEMS FOR AN ELASTIC HALF-PLANE AND THE INFINITE PLATE WITH TWO FINITE ELASTIC OVERLAYS IN THE PRESENCE OF SHEAR INTERLAYERS - Kerobyan, A.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2021)
The problems of contact interaction are observed for an elastic half-plane and the infinite plate, which are strengthened, along the line (in the plane) by two finite overlays (stringers) with different elastic characteristics and constant small thickness. The contact interaction between deformable foundations and overlays is realized through a shear layers (in form of glue layers) having different physical–mechanical properties and geometric configuration. The determination problem of unknown contact stresses are reduced to the systems of Fredholm’s integral equations of the second kind within the different finite intervals, which in the certain region of the change of characteristic parameter typical to the problems, may be solved by the method of successive approximations. Possible particular cases are observed and the character and behavior of contact stresses are illustrated.